Prevalence of parental violence upon girls and its associated factors (Siddhajyoti Interdisciplinary Journal, 2022)
Any form of harm perpetrated by a person to a person within familial relationship is domestic violence. High prevalence of intimate partner violence in districts of province 2 indicates high probability of domestic violence upon children but studies are not focusing it. This paper aims to describe prevalence of parental violence and the association among its associated factors. The study followed cross sectional research design and cluster sampling. Altogether, 435 students participated in the study but data from 385 respondents were submitted for analysis. Tool for data collection was self-administered anonymous questionnaire. Descriptive statistics like percentage, mean and standard deviation were used. Binary logistic regression analysis was used to identify the association among violence committed by parent and its associated factors. This study found that nearly one-third (62.3%) respondents had experience of some type of DV from either mother or father. Relationship of parents, and abusing and beating of mother was highly associated with DV than relationship of parents, and abusing and beating of father. Domestic violence education should be given to parents that focus on relationship of parents.